Faktor-Faktor Yang Berpengaruh Terhadap Pengungkapan CSR Pada Emiten Industri Barang Konsumsi - Helis Safitri Purwanti Ningsih; Dwi Ari Pertiwi (JFAS : Journal of Finance and Accounting Studies, 2023)
The company definitely wants to build a good image for the surrounding environment by giving it responsibility or what is called CSR. This study aims to determine the Effect of Government Share Ownership, Foreign Share Ownership, and Company Size on CSR disclosure in Consumer Goods Industry Issuers Listed on the Indonesia Stock Exchange in 2019-2021. The sample technique used in this study uses purposive sampling and the number of samples are 66 companies listed in the consumer goods industry that are listed on the IDX in 2019-2021. Data analysis using multiple linear regression analysis method. The results of this study indicate that government share ownership has no effect on CSR disclosur.. Foreign share ownership has no effect on CSR disclosure. Firm size has no effect on CSR disclosure